Solidaritas Tokoh Sebagai Budaya Dalam Serial Netflix One Piece - Aditia S, Nida (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
Solidarity is a culture that exists in the Straw Hat pirate group. This culture was born from the habits of Straw Hat members, namely helping each other on the ship so that they cannot be separated. Solidarity can form a very solid friendship that is difficult to break up. Solidarity itself is a system that results from the habits of previous communities, which is in line with the definition of culture. culture in each region is different and can be influenced by various factors, including the location of the region and the living environment.